Mūlamadhyamakakārikā: Introduction and the Spread of its system of Teaching and Learning in India and Tibet (Bodhi Path, 2021)
Nāgārjuna, a second centurion Indian Buddhist adept from Nālandā Mahāvihāra, was the pioneer of the Middle Way Philosophy. As the intent-commentary (āṡaya- vṛtti) of the Prajñāpāramitāsūtra, he composed six treatises on the Middle Way. In this treatise, he elucidates the directed presented order of emptiness (Śākṣanidarṡana-Śūnyatākrama), i.e., the view point of the Prajñāpāramitāsūtra.The treatise titled Mūlamadhyamakakārikā, rendered into English as ‘Fundamental Verses on the Middle Path’, is a key text of Madhyamaka School as well as the masterpiece work of Nārārjuna. He presents the futility of metaphysical speculations in Mūlamadhyamakakārikā utilizing the Buddha’s theory of “dependent origination”. His method of dealing with such metaphysics is referred to as “Middle Path”. It is the middle path that avoids the substantialism of the Sarvāstivādins as well as the nominalism of the Sautrāntikas.
Keywords: Mūlamadhyamakakārikā; Nāgārjuna